2009
DOI: 10.1270/jsbbs.59.519
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Triticeae seed storage proteins for improvement of wheat end-product quality

Abstract: The seed storage proteins (SSPs) of cultivated wheat (Triticum aestivum and T. durum), namely, glutenin and gliadin, impart viscoelastic properties to bread dough, making wheat well suited for bread-making. Extensive studies on wheat SSPs have been carried out and revealed genetic diversity among wheat cultivars. Here, we review the studies of SSPs from more exotic species in the Triticeae tribe, primarily based on our own recent studies. SSPs of barley (Hordeum vulgare), homologous to those in wheat, exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…Some of these lines have been adopted into practical breeding programs as materials for disease or insect resistance (Jiang et al, 1994;Friebe et al, 1996). Some other lines with single alien chromosomes may also be used for improvements in bread making quality, because some lines express novel seed storage proteins (Garg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these lines have been adopted into practical breeding programs as materials for disease or insect resistance (Jiang et al, 1994;Friebe et al, 1996). Some other lines with single alien chromosomes may also be used for improvements in bread making quality, because some lines express novel seed storage proteins (Garg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Genes located on chromosome 1V of Dasypyrum villosum in both addition (De Pace et al 2001) and translocation lines had also largely positive effects on bread-making quality. Furthermore, Garg et al (2009b) found that seed storage proteins of Th. intermedium had positive effects when transferred to wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to fungal and viral disease, drought and heat tolerance and its perennial nature has made Agropyron intermedium an attractive genetic donor species for bread wheat. Triticum ‐ Agropyron substitution lines have been developed and used but successful introgressions are rare because of undesirable gene linkages and instability of larger chromosome fragments (Friebe et al, 1996; Garg et al, 2008; Khan, 2000; Sibikeev et al, 1995). Mujeeb‐Kazi et al (1989) hand pollinated several varieties of bread wheat (Chinese Spring, Glennson 81, Nacozari‐76, and Pavon‐76) and A. intermedium in the field.…”
Section: Wild Canadian Species At Potential Risk For Crossing With Trmentioning
confidence: 99%